Nutritional Status, Eating Behavior and Physical Activity among Students at the Faculty of Humanities, Chiang Mai University - Porniammongkol, Orraya (Journal of Nutrition Association of Thailand (Online), 2021)
This research aimed to evaluate nutritional status, eating behaviors and physical activities among undergraduate students of Faculty of Humanities, Chiang Mai University. This is a cross-sectional study using a convenient sample by public announcement for volunteers. Four hundred students, 26.2% males and 73.8% females, were included in the study. Nutritional status was assessed by body mass index (BMI) using Asian adult criteria for nutritional status classification. Eating behavior and lifestyle physical activities were assessed using questionnaires and evaluated by rating scales of 4 points Likert Scale (1=need improvement to 4=very good). Energy intake of the students were assessed by one-day 24 hours dietary recall and energy intake calculated using INMUCAL-Nutrients V. 3.0 Program. The results revealed that overweight (BMI 23.0-24.9), obese I (BMI 25.0-29.9) and obese II (BMI > 30) were 14, 7 and 3 %, respectively. Overweight and obesity were greater among males (38%) than that of females (20%), whereas less underweight among males (16.2%) than females 24.1 (p <.001). Overall mean energy intake was 1,250+748 kcal per day and not significantly different between males and females. Overall average scores on eating behaviors and lifestyle activities were considered good (2.61±0.24 and 2.79±0.32, respectively). Among the eating behavior or physical activity which the average scores were good, for some behaviors, more than 50% of students were below the acceptable scores. Obese group (BMI>30 kg/m2) had significantly lower scores on eating more at dinner than lunch/ breakfast, and spending over 2 hours per day on computer game compared with other BMI groups (p<0.01 and p<0.05, respectively).